Infection of Neospora caninum in cattle and dogs: A narrative review (Research, Society and Development, 2026)
Neospora caninum is an obligate intracellular protozoan belonging to the phylum Apicomplexa, widely recognized as one of the main agents associated with reproductive disorders in cattle and neuromuscular manifestations in dogs. Since its first description in the 1980s, the parasite has aroused growing interest due to the clinical, epidemiological, and economic impact associated with infection. Dogs act as definitive hosts, while cattle and other species function as intermediate hosts, which contributes to the complex dynamics of transmission and persistence of the disease in different production environments. The high efficiency of vertical transmission in cattle, combined with the wide geographic distribution of the parasite, reinforces its importance for animal health. The objective of this review is to gather and present the main advances related to morphology, biological cycle, transmission, clinical manifestations, diagnostic methods, treatment, and control strategies, focusing on cattle and dogs, highlighting essential elements for the understanding and reduction of the impact of neosporosis.